Use of biological indicators of soil health to estimate reactive nitrogen dynamics in long-term organic vegetable and pasture systems. (December 2016) - Bhowmik, Arnab; Fortuna, Ann-Marie; Cihacek, Larry J.; Bary, Andy I.; Cogger, Craig G.
Abstract: Diverse crop rotations, cover crops and the possibility of integrating livestock make organic systems potentially more sustainable than other agroecosystems. Lower reactive nitrogen (N) in organic systems minimizes the potential for N losses. However, addition of organic manures and residues containing mineralizable N and carbon (C) have the potential to enhance nitrous oxide (N2 O) emissions. We conducted a 39 d laboratory incubation to assess key microbiological drivers controlling nitrification and denitrification in long-term organic agroecosystems during simulated freeze-thaw cycles. Soils were collected from two annual organic vegetable systems receiving 1) mixed-compost, or 2) broiler litter and 3) an organic perennial pasture system cropped to vegetables every third year. Soil microcosms amended with 15 N labelled sugar beet residue or unamended were maintained at 40, 60 and 80% of water filled pore space (WFPS). Significant N2 O was emitted (4287–6138 μg kg −1 soil) via denitrification from amended soil microcosms at 3 °C and 80% WFPS. Archaeal (AOA) and bacterial (AOB) nitrifier amoA gene copies were affected by temperature and reactive N species during freeze-thaws. Long-term organic vegetable cropping systems receiving mixed-compost additions had the potential to accumulate C and immobilize excess reactive soil N (particularly nitrates) thereby improving soil health and reducing N2 O emissions. Highlights: Relative copies of amoA genes in AOA, AOB vary with organic system and climate. amoA genes are indicators of soil health, biogeochemical cycles, reactive N losses. Mixed-compost additions reduce inorganic N and N2 O in organic vegetable systems.